PARENTAL ATTACHMENT PATTERNS AND THEIR IMPACT ON SEPARATION ANXIETY IN KINDERGARTEN CHILDREN - Mellal Safia; Belkheir Faiza (International Journal of Innovative Technologies in Social Science, 2025)
The current study aims to examine the impact of parental attachment patterns on the emergence of separation anxiety in kindergarten children. To achieve this aim, a clinical study was conducted involving five children enrolled at Toyour Al-Jannah Kindergarten in Relizane, aged between three and five years. The Separation Anxiety Scale (prepared by Maiar Mohamed Ismail, 2013) and the Parental Attachment Patterns Scale (prepared by Mervat Azmy Zaki Abdel-Gawad, 2015) were administered to these children. The study concluded that insecure parental attachment patterns (fearful attachment, dismissive attachment, and preoccupied attachment) influenced the emergence of separation anxiety among kindergarten children.